Pregnancy in an Asymptomatic Woman with Porencephalic and Arachnoid Cysts - Franco Pepe; Gianmarco Marchese; Gabriele Giuseppe Pepe; Elisabetta Zambrotta; Giulio Insalaco; Claudia Garraffo; Valeria La Rosa (Hindawi Limited, 2020)
A 25-year-old woman presented to the obstetric clinic in her first pregnancy. The patient was accompanied by her mother who reported an episode of intracerebral hemorrhage after birth and also remembered access to the emergency department after generalized tonic-clonic seizure as an infant. She was not able to describe the therapy for seizure preventions and even when and why it was suspended, but she affirmed that no residual neurological consequences were detected in the following years. Actually, the pregnant woman was in good health without neurological symptoms nor assumed any therapy. A neurologist reviewed the patient's CT scan in which arachnoid cyst and porencephalic cyst were evident, and he assessed that no abnormalities were found in motor, sensory, and mental state examination. EEG did not show any epileptiform or seizure-like activity. No antiepileptic drug was prescribed due to the absence of symptoms since many years. The patient had no neurological symptoms during pregnancy or obstetric complications and delivered at term a healthy baby through a caesarean section. She breastfed, and after two years, the patient and the baby are healthy. The association of porencephalic and arachnoid cyst in pregnancy is an extremely rare neurological condition that needs a multidisciplinary counseling in pregnancy, but an uneventful course is possible.